ANALISIS PENGENDALIAN KUALITAS PRODUK PADA KONVEKSI NITRA JAYA DI KABUPATEN BADUNG - Sadukari, I Made Adhi Nugraha; Mandala, Kastawan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023DO - 10.24843/EEB.2023.v12.i09.p09, 2023)
Declining product quality often occurs during the production process which can affect product quality. Damaged products can be done by the company by controlling the quality of the products produced through many methods such as DMAIC (Define, Measure, Analyze, Improve and Control), Six Sigma and Statistical Quality Control (SQC). This research was conducted at the Nitra Jaya Convection which is located on Jalan Raya Panglan, Banjar Cepaka Kapal, Mengwi District, Badung Regency, Bali. The data analysis technique used is statistical quality control (SQC) by using tools such as check sheets, P-charts, Fishbone diagrams and Quality Costs. The results of the analysis of the cost of production quality at the Nitra Jaya Convection for the 2019 period still show that the actual quality costs incurred by the company are still greater than the optimal quality costs that should be incurred by the company. The actual damage was 116 pcs of uniforms, with a total cost of quality (TQC) of Rp13.244.958 . The lowest point or the optimal point of quality costs is at the damage limit of 1 95 pcs of uniforms with an optimum total cost of quality (TQC) of Rp11.647.055 . This shows that quality control has not been implemented optimally.